Qualitative analysis of the subcontract bidding process in mining projects - Araya , Felipe; Perez, Jocelyn; Salazar, Luis; Olivari , Valeria (Revista Ingeniería de Construcción, 2024)
Chile is the fifth largest economy in Latin America and one of its main economic activities is mining, a sector in which subcontracting has grown exponentially in the last decade. However, despite its importance, the process of awarding subcontracts lacks a deeper understanding that identifies its inefficiencies and opportunities for improvement. This context motivates the study of the subcontract bidding and awarding process within a contractor company in mining projects. A database with real projects was used, comprising 13 projects with an average of 33 subcontracts executed during 2023, complemented by a qualitative content analysis of interviews with 18 experts. This combination of quantitative and qualitative analysis aims to identify critical areas of the current process and propose potential improvements. Our results reveal inefficiencies in the approval and supplier management stages. Proposed improvements include the implementation of training, streamlining of approvals and greater control over suppliers. These results suggest that optimizing the outsourcing process would not only increase efficiency, but also may improve project quality. Future research might focus on modeling subcontracting processes to test potential improvements.